Adherence to fast track measures in colorectal surgery: a survey among German and Austrian surgeons - Willis, Maria; Keller, Peter S.; Sommer, Nils; Koch, Franziska; Ritz, Jörg-Peter; Beyer, Katharina; Reißfelder, Christoph; Hardt, Julia; Herold, Alexander; Buhr, Heinz J.; Emmanuel, Klaus; Kalff, Joerg C.; et al. (International journal of colorectal disease, 2023)
The effectiveness of modern perioperative treatment concepts has been demonstrated in several studies and meta-analyses. Despite good evidence, limited implementation of the fast track (FT) concept is still a widespread concern. To assess the status quo in Austrian and German hospitals, a survey on the implementation of FT measures was conducted among members of the German Society of General and Visceralsurgery (DGAV), the German Society of Coloproctology (DGK) and the Austrian Society of Surgery (OEGCH) to analyze where there is potential for improvement.
Gesehen am 24.07.2024